Small fiber neuropathy: clinical presentation, diagnostic methods, possibly causes and treatment - E. Paulėkas; D. Garšvienė; K. Petrikonis (Neurologijos seminarai)
Small fiber neuropathy (SFN) is a disorder affecting the thin myelinated Aδ and unmyelinated C nerve fibers, which usually presents clinically with symmetrical, length-dependent neuropathic and autonomic symptoms. In some cases, a non-length-dependent clinical presentation may develop instead, characterized by focal or multifocal symptoms. Diagnosis of pure SFN remains difficult in situations when no pathological findings are detected during nerve conduction tests (using standard electroneuromyography) and patients present with unusual subjective symptoms. However, quantitative measurement of intraepidermal nerve fiber density (INFD) in skin biopsy and quantitative evaluation of sensory or autonomic symptoms may facilitate the diagnostic process. There is a plethora of possible SFN causes, such as metabolic, immune system mediated or neurotoxic factors, although in about 50% of cases, the precise etiology remains unknown. In recent years, mutations in genes SCN9A and SCN10A that encode voltage-gated sodium channels Nav1.7 and Nav1.8, respectively, have been linked to nearly a third of SFN cases that previously were thought of as idiopathic. In clinical practice, it is important to identify possible SFN causes and prescribe medications that not only treat the symptoms but directly intervene in the etiopathogenetic mechanisms of the disorder itself. In this review, we examine clinical signs, possible causes, available diagnostic methods and treatment of SFN.